2013
DOI: 10.4161/psb.22508
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted roles ofArabidopsisPP6 phosphatase in regulating cellular signaling and plant development

Abstract: Protein phosphorylation and dephosphorylation mediated by kinases and phosphatases are major reversible post-translational modifications used to regulate many cellular processes. In eukaryotes, up to a third of proteins are regulated by protein phosphorylation. The genomes of eukaryotes encode a large number of kinases and phosphatases. For example, the human genome encodes at least 518 putative protein kinases that can be generally classified into two families: 90 protein tyrosine (Tyr) kinases (PTKs) and 428… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…As a catalytic subunit of protein phosphatase, TOPP4 must bind to different regulatory subunits to form a functional enzyme to participate in multiple signaling pathways (Tian and Wang, 2002). Because the regulatory subunits of phosphatases are dynamic at different developmental stages or in response to various environmental signals (Dai et al, 2013), PP1 and PP6 may respond to different developmental signals in different organs or tissues at various developmental stages. The topp4-1 mutant showed PC defects only in and after the third true leaves, whereas the fypp1 mutant has PC defects in cotyledons and true leaves (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As a catalytic subunit of protein phosphatase, TOPP4 must bind to different regulatory subunits to form a functional enzyme to participate in multiple signaling pathways (Tian and Wang, 2002). Because the regulatory subunits of phosphatases are dynamic at different developmental stages or in response to various environmental signals (Dai et al, 2013), PP1 and PP6 may respond to different developmental signals in different organs or tissues at various developmental stages. The topp4-1 mutant showed PC defects only in and after the third true leaves, whereas the fypp1 mutant has PC defects in cotyledons and true leaves (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PP6 regulates the activities of many host proteins (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and it is therefore possible that PP6 silencing perturbs the virus life cycle by affecting other cellular processes. However, the fact that PP6 interacts directly with the viral RdRP suggests that it plays a direct role in the viral life cycle by regulating the posttranslational modifications of viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PP6 is a member of the PP2A subfamily of protein phosphatases, cellular enzymes that catalyze the liberation of inorganic phosphate from proteins and peptides at serine or threonine residues (22). PP6 is a significant regulator of a number of cellular processes, including chromosome stability and the DNA damage response (23)(24)(25)(26)(27), mitosis and the regulation of cell cycle progression (22,(28)(29)(30)(31), signaling (32,33), pre-mRNA splicing (34), and vesicular trafficking (35). The catalytic subunit PPP6C and the regulatory subunits PPP6R1 and PPP6R3 were found to copurify with the viral RdRP.…”
mentioning
confidence: 99%
“…In a recent study, we showed that Arabidopsis FyPP1 (for Phytochrome-associated serine/threonine protein phosphatase1) and FyPP3, two homologous catalytic subunits of PP6, physically interact with SAL (for SAPS-domain like protein) and PP2AA proteins (RCN1/PP2AA1, PP2AA2, and PP2AA3) to form a PP6-type heterotrimeric holoenzyme that directly regulates the phosphorylation status of PIN-FORMED (PIN) proteins (auxin efflux carriers) and subsequently affects auxin efflux and plant development (Dai et al, 2012a(Dai et al, , 2012b. In this study, we extend these findings by showing that FyPP also plays a critical role in regulating ABA signaling in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%